2009
DOI: 10.1002/hbm.20780
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of piece‐wise linear, linear, and nonlinear atlas‐to‐patient warping techniques: Analysis of the labeling of subcortical nuclei for functional neurosurgical applications

Abstract: Digital atlases are commonly used in pre-operative planning in functional neurosurgical procedures performed to minimize the symptoms of Parkinson's disease. These atlases can be customized to fit an individual patient's anatomy through atlas-to-patient warping procedures. Once fitted to pre-operative magnetic resonance imaging (MRI) data, the customized atlas can be used to plan and navigate surgical procedures. Linear, piece-wise linear and nonlinear registration methods have been used to customize different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
80
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 68 publications
(81 citation statements)
references
References 64 publications
1
80
0
Order By: Relevance
“…The estimation error was 1.96 mm when using an ACPC alignment strategy and 1.72-1.77 mm with nonlinear matching algorithms. A study by Chakravarty et al 34 revealed that the Talairach coordinate-based targeting misplaced the thalamus outlines by 2.44 Ϯ 0.68 mm. There is converging evidence that image-based atlas-to-patient alignment tools outperform methods like the ACPC alignment technique; this was also indicated by our postmortem evaluations.…”
Section: Discussionmentioning
confidence: 99%
“…The estimation error was 1.96 mm when using an ACPC alignment strategy and 1.72-1.77 mm with nonlinear matching algorithms. A study by Chakravarty et al 34 revealed that the Talairach coordinate-based targeting misplaced the thalamus outlines by 2.44 Ϯ 0.68 mm. There is converging evidence that image-based atlas-to-patient alignment tools outperform methods like the ACPC alignment technique; this was also indicated by our postmortem evaluations.…”
Section: Discussionmentioning
confidence: 99%
“…Decline in the entire DBS group (containing both CN and no CN penetration) was given (compared to the best medical treatment) without subdividing for CN penetration. Normalization of the data was applied, which facilitated comparisons between subjects; however, the individual interrelationship between DBS trajectory and CN was lost [9, 17]. Taking the findings of Isler et al [11] into account, these differences are possibly due to short-term follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…To summarize the technique, 3D reconstruction of serial histological data for the striatum, pallidum, and thalamus were warped to an MRI-based template (19). The atlases were then customized to a subset of the dataset (30 randomly selected subjects) using a nonlinear transformation estimated in a region-of-interest defined around the subcortical structures (17,19,74,75). This set of subjects then acts as a set of templates to which all other scans are warped.…”
Section: Methodsmentioning
confidence: 99%